Synthesis and characterization of Pt-CMK-3 hybrid nanocomposite for hydrogen storage - Juarez, Juliana (2015)
The nanometric carbon CMK-3 modified with Pt was synthesized and applied as a reservoir for hydrogen uptake. We found that the newly synthesized hybrid composites exhibited significantly enhanced H2 storage. The approach that we have followed includes synthesis of nanostructures with the experimental study of its adsorption capacity and storage properties. In summary, we have shown that CMK-3 ordered porous carbon modified with Pt nanoclusters is a promising material for hydrogen uptake. The samples were characterized by X-ray diffraction, N2 isotherms, X-ray photoelectron spectra and transmission electron microscopy. The nanoparticles of Pt (~1.7nm) incorporated onto the nanostructured carbon CMK-3 showed higher hydrogen uptake at low and high pressures (3.3wt% of H2 sorption at 10bar and 77K) than CMK-3.